Motivasi dan Disiplin: Kunci Produktivitas Kerja di Dinas Lingkungan Hidup Kota Surakarta - Aprilia Widya Cahyaningrum; Esti Dwi Rahmawati; Khabib Alia Akhmad (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This research aims to analyze the role of motivation and work discipline on work productivity at the Environmental Office. The population in this study comprises all employees of the Environmental Office, and the sample size used in this study is 51 respondents. The variables used in this research are work discipline, work productivity, and motivation. The data used in this study is primary data. The data collection method employed is a questionnaire. The data analysis technique used is Structural Equation Modeling-Partial Least Square (SEM-PLS) with SmartPLS 4.0. The results of this study indicate that motivation has a positive and significant effect on work productivity, and work discipline has a positive and significant effect on work productivity.